(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The use of electrical technologies (ozonation of the drying agent, saturation of the air with air ions, use of electro-osmosis) is an additional external controlled effect on the chopped wood. This makes it possible to control the drying process more flexibly. With fairly low energy consumption, electrical technology can significantly affect the value of conditional entropy. By controlling the magnitude of the electrical technology influence, it is possible to control the reaction to the main external influence - the drying agent. The analysis of the behavior of shredded wood, its reaction to external influences allows us to say that those periods of external influence when the reaction is in the phase of preventive inhibition are more effective for its drying. It is in this state that the shredded wood uses its internal energy to fulfill the goals of the drying process. The principle of maximum information leads to the main techniques, the use of which in drying will give the effect of resource saving. It has been established that to control the process of active ventilation, it is desirable to measure the temperature and humidity of the air at the inlet and outlet of the layer. It has been established that to control the process of active ventilation, it is desirable to measure the temperature and humidity of the air at the inlet and outlet of the layer. For the calculation of drying by active ventilation, the well-known step method, which is based on a simplified mechanism of heat and mass transfer, was used as the most accessible. In accordance with the principle of maximum information, based on the results of modeling the drying process by active ventilation, it is proposed to increase the fan performance at times when the relative humidity is less than 65%. During the simulation, it was found that the drying time when adjusting the fan performance is 4.7 times shorter than with the conventional ventilation method. Drying unevenness remains at the same level or is reduced to 1%.